Self-rated health, generalized trust, and the Affordable Care Act: A US panel study, 2006–2014. (October 2017) - Mewes, Jan; Giordano, Giuseppe Nicola
Abstract: Previous research shows that generalized trust, the belief that most people can be trusted, is conducive to people's health. However, only recently have longitudinal studies suggested an additional reciprocal pathway from health back to trust. Drawing on a diverse body of literature that shows how egalitarian social policy contributes to the promotion of generalized trust, we hypothesize that this other 'reverse' pathway could be sensitive to health insurance context. Drawing on nationally representative US panel data from the General Social Survey, we examine whether the Affordable Care Act of 2010 could have had influence on the deteriorating impact of worsening self-rated health (SRH) on generalized trust. Firstly, using two-wave panel data (2008–2010, N = 1403) and employing random effects regression models, we show that a lack of health insurance coverage negatively determines generalized trust in the United States. However, this association is attenuated when additionally controlling for (perceived) income inequality. Secondly, utilizing data from two separate three-wave panel studies from the US General Social Survey (2006–10; N = 1652; 2010–2014; N = 1187), we employ fixed-effects linear regression analyses to control for unobserved heterogeneity from time-invariant factors. We demonstrate that worsening SRH was a stronger predictor for a decrease in generalized trust prior (2006–2010) to the implementation of the Affordable Care Act. Further, the negative effect of fair/poor SRH seen in the 2006–2010 data becomes attenuated in the 2010–2014 panel data. We thus find evidence for a substantial weakening of the previously established negative impact of decreasing SRH on generalized trust, coinciding with the most significant US healthcare reforms in decades. Social policy and healthcare policy implications are discussed. Highlights: Lack of health insurance negatively correlated with generalized trust. Controlling for income, health insurance coverage does not impact generalized trust. The negative effect of fair/poor SRH on generalized trust was stronger pre -ACA. The negative effect of SRH on generalized trust was statistically insignificant post -ACA. More egalitarian healthcare systems could contribute to sustaining social capital.